Language Use in YOASOBI’s Song Lyrics: A Psycholinguistic Study Based on Samuel Beckett’s Theory of Pain - Nadya Eva Pradini; Via Luviana Dewanty; Sugihartono Sugihartono (Vocational College of Diponegoro University, 2026)
Mental health issues are one of the most significant topics in modern society and are often expressed through artistic works, including music. The songs in YOASOBI’s albums highlight this theme through emotionally charged lyrics. This study aims to analyze the use of language in YOASOBI’s song lyrics, specifically Yoru ni Kakeru, Encore, Kaibutsu, and Idol through a psycholinguistic approach, employing Samuel Beckett’s theory of pain. The research focuses on integrated linguistic markers, specifically lexical choices (diction), figurative devices (metaphor, paradox, and chiasmus) as primary data to bridge the gap between lyrical construction and the psychological state of the subjects. This study applies a psycholinguistic analysis using a descriptive qualitative method, with data drawn from song lyrics, music videos, questionnaire responses, and YouTube listener comments. The findings reveal that the linguistic elements in the lyrics reflect inner experiences filled with emotional suffering, resonating with Beckett’s philosophical view. These findings suggest that song lyrics can serve as a medium to articulate psychological struggles through deep linguistic constructions. However, this research remains limited to songs analyzed alongside YouTube comment responses. Therefore, future studies are encouraged to explore more works with similar themes to contribute further to the fields of language, psychology, and cultural studies.